ANALYSIS OF FACTORS AFFECTING ROAD TRANSPORT ACCIDENTS - A. Sorokin; S. Yakovlev; A. Orlova (Вестник Северо-Кавказского федерального университета, 2022)
The article examines the approaches to the determination of risk factors in road traffic accidents, describes groups of risk indicators, examines various points of view. The approaches to the assessment of a set of risk factors are considered. From the point of view of assessment, objective and subjective factors are analyzed. It is pointed out that objective factors are sufficiently amenable to assessment and adjustment using control actions. The study offactors affecting road safety is the basis for the development of control actions.